Impact of structural and process quality indicators on the outcomes of acute aortic dissection. (30th August 2020) - Yamaguchi, Tetsuo; Nakai, Michikazu; Sumita, Yoko; Miyamoto, Yoshihiro; Matsuda, Hitoshi; Inoue, Yousuke; Yoshino, Hideaki; Okita, Yutaka; Minatoya, Kenji; Ueda, Yuichi; Ogino, Hitoshi
Abstract: OBJECTIVES: The mortality of acute aortic dissection (AAD) remains high, and evidence-to-practice gaps exist in real-world treatment. We explored the first quality indicators (QIs) for AAD management and evaluated the associations between the achievement of these QIs and the outcome in a nationwide administrative database. METHODS: A systematic search was performed to establish initial index items for QIs. An evaluation was performed through an expert consensus meeting using the Delphi method. We studied 18 348 patients who had AAD (type A: 10 131; type B: 8217) in the Japanese Registry of All Cardiac and Vascular Diseases database between April 2012 and May 2015. The associations between the achievement of QIs [categorized into tertiles (low, middle and high)] and in-hospital mortality were determined by multivariable mixed logistic regression analyses. RESULTS AND CONCLUSION: We developed a total of 9 QIs (5 structural and 4 process). Lower achievement rates of QIs were significantly associated with higher in-hospital mortality in both types [type A = middle: odds ratio (OR) 4.03; 95% confidence interval (CI) 3.301–4.90; P < 0.001; low: OR 15.68; 95% CI 11.67–21.06; P < 0.001 vs high; type B = middle: OR 3.48; 95% CI 2.19–5.53; P < 0.001; low: OR 7.79; 95% CI 4.65–13.06; P < 0.001 vs high]. Various sensitivity analyses showed consistent results. High achievement rates of QIs were significantly associated with reduced in-hospital mortality. Evaluating each hospital's management using QIs would help to equalize treatment quality and demonstrate the evidence-to-practice gaps in real-world treatments for AAD. Abstract : Although current guidelines [1–3] provide evidence-based recommendations for the management of acute aortic dissection (AAD), the mortality of AAD remains high [4].